Enhancing the quality of self-organized nanoripples by Ar-ion bombardment of a bilayer system. (29th June 2021) - Li, Jinyu; Yang, Gaoyuan; Bradley, R Mark; Liu, Ying; Frost, Frank; Hong, Yilin
Abstract: Ion bombardment (IB) is a promising nanofabrication technique for producing nanoripples. A critical issue that restricts the application of IB is the limited quality of IB-induced nanoripples. Photoresist (PR) and antireflection coating (ARC) are of technological relevance for lithographic exposure processes. Moreover, to improve the quality of IB-induced self-organized nanoripples, in this study, a PR/ARC bilayer was bombarded at an incidence angle of 50°. The surface normalized defect density and power spectral density, obtained via scanning atomic force microscopy, indicate the superiority of the PR/ARC bilayer nanoripples over those of single PR or ARC layers. The growth mechanism of the improved nanoripples, deciphered via the temporal evolution of the morphology, involves the following processes: (i) formation of a well-grown IB-induced nanoripple prepattern on the PR, (ii) transfer of nanoripples from the PR to the ARC, forming an initial ARC nanoripple morphology for subsequent IB, and (iii) conversion of the initial nonuniform ARC nanoripples into uniform nanoripples. In this unique method, the angle of ion-incidence should be chosen so that ripples form on both PR and ARC films. Overall, this method facilitates nanoripple improvement, including prepattern fabrication for guiding nanoripple growth and sustainable nanoripple development via a single IB. Thus, the unique method presented in this study can aid in advancing academic research and also has potential applications in the field of IB-induced nanoripples.